Organizing the Professional Career of the Employee in Algerian Legislation - Hocine, Nouara (The Arab Journal of Administration, 2018)
Human resources, which concern with organization of professional path of employees is one of most important aspect of administration because of concentration on employees, as they not only consider rare resource but also the most effective element at all in productivity. Which we have to administrate and develop it with effect and coefficient way to grant return and superiority in performance in both short and long terms. From the department of employees to the individual administration, then the employee’s affairs department and finally the administration of human resources, and across all these stages, acquire the employer, the clerk and the human resource their importance. The first terminology connected with worker as an employee and changed when philosophy and wieu towards him has been changed by existing what we call the administration of human resources, and the employee became a mental capital instead of a hired worker. The administration of human resources consists of a collection of activities, which aim to push creatives and abilities to contribute in achieving the letter the vision the strategy and the organizational aims. So the vule of human resources administration consider a corner stone in majority of administrations because it aims to consolidate the organizational abilities through thepolariztion and qualification the suitable skills to current and future challenges and sustain in front of competivity and have ability to adapt with alternations which characterize the globalization and modernization of administration and all of her aspects of life. So guiding and controlling of the professional route for employees need to a curate planning based on principals and basies applied with the human resources administration, through which it can generates the utmost energy of the employee from the moment of selecting him to the end of professional relation across different stages of his professional age.